2009
DOI: 10.1063/1.3100206
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement effect on the effective mass in two-dimensional electron gas of AlGaN/GaN heterostructures

Abstract: We report the results of direct measurements and a theoretical investigation of the in-plane effective mass in the two-dimensional electron gas of nominally undoped AlGaN/GaN heterostructures with a different degree of quantum confinement. It is shown that in most cases the conduction band nonparabolicity effect is overestimated and the electron wave-function penetration into the barrier layer should be taken into account. The contribution of the wave-function hybridization is determined to play the dominant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 39 publications
5
28
0
Order By: Relevance
“…4 as an example. In our analysis we observed that the m * values obtained from linear fitting are consistently higher than those obtained from non-linear curve fit as also reported by Kurakin et al 13 The quantum scattering time is contained in the exponential term in Eq. (1) and signifies the growth of the amplitude of oscillations with magnetic field.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…4 as an example. In our analysis we observed that the m * values obtained from linear fitting are consistently higher than those obtained from non-linear curve fit as also reported by Kurakin et al 13 The quantum scattering time is contained in the exponential term in Eq. (1) and signifies the growth of the amplitude of oscillations with magnetic field.…”
Section: Resultssupporting
confidence: 71%
“…1. the 1 st subband are consistently higher for both the samples and are in the same range as reported in earlier studies such as by Kurakin et al 13 In this context attention is drawn towards the location of electron wave function for the two sub bands in GaN/AlGaN HEMT Structures. The Electron wave functions for two samples as deducted from the 1D Schrodinger Poisson solver 16 is depicted in Fig.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations